91 THE DEVELOPMENT OF MURINE TUMOR ANIMAL MODELS FOR OVARIAN CANCER INCORPORATING A TUMOR-SPECIFIC SPERM 17/CANCER TESTIS ANTIGEN. (1st January 2006) - Kyle, A. S.; Grizzi, F.; Wan, W.; Micheal, S. H.; Lowe, D. B.; Cobos, E.; Kennedy, R. C.; Chiriva-Internati, M.
Abstract : Purpose: An experimental pulmonary metastatic model for ovarian cancer has still not been developed. Here we introduce tumor models in NOD/SCID mice for ovarian cancer incorporating a tumor-specific Sp17/CT antigen. Methods: Ovarian adenocarcinoma cells (SKOV-3) were intraperitoneally injected in an attempt to demonstrate a seeding of the organs located in the peritoneal cavity. Examination of the ovaries for the progression of the disease was marked by an increase of the size of the growing tumor. Following intravenous injection, viable SKOV-3 cells were recovered by primary organ cell culture in the liver, lungs, ovaries, abdomen, and ascites. Summary: The presence of SKOV-3 cells in these tissues was confirmed by RT-PCR and immunocytochemistry using the sperm protein 17 (Sp17). The number and size of tumoral foci were quantified using a computer-aided model. Tumoral foci were observed in the lungs of tumor-bearing mice and they are dependent on the dose of injected SKOV-3 cells and time after injection. Conclusion: The quantification of the number of lung tumoral foci and the detection of distant metastasis might provide specific reference points for examining the mechanism(s) of the immune response to Sp17 and for evaluating immunologically based therapies within this novel ovarian murine tumor model.